1986
DOI: 10.1590/s0037-86821986000400003
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento da cepa LE de Schistosoma mansoni, após passagem em hospedeiro humano infectado acidentalmente

Abstract: Uma auxiliar de laboratório infectou-se acidentalmente, com cercárias de Schistosoma mansoni, cepa LE, mantida rotineiramente em nossos laboratórios. Decorridos 5 meses, o exame parasitológico de fezes revelou 108 ovos/g . A pacientefoi tratada com oxamniquine, porém a infecção continuou ativa (6 ovos/g). Foi então obtido o isolado SSF mantido no modelo Biomphalaria glabrata - camundongo albino. Os resultados obtidos no estudo comparativo, entre o isolado SSF e a cepa LE, que lhe deu origem, mostraram que a du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Mann-Whitney test was performed to compare the granuloma area, and two-way ANOVA followed by Bonferroni's post-test was performed to compare hydroxyproline concentrations between the groups. adult worm recovery rate in experimental infections with the human-isolated parasite was even higher, reaching 31-34% (Katz et al, 1973;Araújo et al, 1986), dropping to 20-25% in recent publications (Maggi et al, 2021;Oliveira et al, 2022), a rate similar to that observed in the current study. Therefore, published data confirm that the long-term maintenance of S. mansoni from the LE strain under laboratory conditions contributes to modifying the infectivity rate of the parasite; however, it attenuated the difference between LE and HS parasite strains, indicating that the original host has an important role in this biological aspect of the parasite strain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mann-Whitney test was performed to compare the granuloma area, and two-way ANOVA followed by Bonferroni's post-test was performed to compare hydroxyproline concentrations between the groups. adult worm recovery rate in experimental infections with the human-isolated parasite was even higher, reaching 31-34% (Katz et al, 1973;Araújo et al, 1986), dropping to 20-25% in recent publications (Maggi et al, 2021;Oliveira et al, 2022), a rate similar to that observed in the current study. Therefore, published data confirm that the long-term maintenance of S. mansoni from the LE strain under laboratory conditions contributes to modifying the infectivity rate of the parasite; however, it attenuated the difference between LE and HS parasite strains, indicating that the original host has an important role in this biological aspect of the parasite strain.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the host species from which the parasites were originally isolated (human vs wild rodent), the long-term maintenance of the LE parasite strain could also have contributed to the biological differences in the current study. Nevertheless, analysing data from published works that investigated the infectivity rate of the LE strain of S. mansoni in mice over the years, we observed that, just after the isolation, the adult worm recovery rate in experimental infections with the human-isolated parasite was even higher, reaching 31–34% (Katz et al , 1973; Araújo et al , 1986), dropping to 20–25% in recent publications (Maggi et al , 2021; Oliveira et al , 2022), a rate similar to that observed in the current study. Therefore, published data confirm that the long-term maintenance of S. mansoni from the LE strain under laboratory conditions contributes to modifying the infectivity rate of the parasite; however, it attenuated the difference between LE and HS parasite strains, indicating that the original host has an important role in this biological aspect of the parasite strain.…”
Section: Discussionmentioning
confidence: 96%